2012
DOI: 10.2174/138920112800624346
|View full text |Cite
|
Sign up to set email alerts
|

Is the Use of Autologous Platelet-Rich Plasma Gels in Gynecologic, Cardiac, and General, Reconstructive Surgery Beneficial?

Abstract: Tissue repair at wound sites begins with clot formation, and subsequently platelet degranulation with the release of platelet growth factors, which are necessary and well-regulated processes to achieve wound healing. Platelet-derived growth factors are biologically active substances that enhance tissue repair mechanisms, such as chemotaxis, cell proliferation, angiogenesis, extracellular matrix deposition, and remodeling. This review describes the biological background and results on the topical use of autolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 53 publications
0
49
0
Order By: Relevance
“…The relevance of platelets and their products for successful tissue reconstitution is reflected in the use of platelet-rich plasma (PRP) to promote healing (53)(54)(55). However, rendering mice thrombocytopenic leads to increased wound inflammation without affecting the reparative aspects of wound repair (56).…”
Section: Figurementioning
confidence: 99%
“…The relevance of platelets and their products for successful tissue reconstitution is reflected in the use of platelet-rich plasma (PRP) to promote healing (53)(54)(55). However, rendering mice thrombocytopenic leads to increased wound inflammation without affecting the reparative aspects of wound repair (56).…”
Section: Figurementioning
confidence: 99%
“…In addition, increasing data indicate that platelets are also involved in fundamental processes of vascular biology, such as angiogenesis, tissue regeneration, and tumor metastasis. [1][2][3][4] Platelets promote new blood vessel growth via numerous stimulators of angiogenesis. For example, vascular endothelial growth factor, fibroblast growth factor, and platelet-derived growth factor can induce endothelial cell proliferation and cell migration, stimulate chemotaxis, and increase tubule formation.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were in agreement with the study of Harris et al(2012) [40] who injected PRP or saline solution into a variety of none injured muscle tissues of healthy rabbits and histologically evaluated the specimens after 2, 6 and 12 weeks. They reported that PRP initially promotes intensification of the inflammatory process in muscle injuries because this inflammatory phase is a very important step during muscle healing as it triggers the wound healing cascade leading to the cellular migration and proliferation, glycosaminoglycan and collagen deposition, collagen maturation and remodeling of the tissue [41] .The neutrophils and monocytes have granules filled with myeloperoxidase that contributes to the antimicrobial action of PRP [42] . [42] who used platelet-rich fibrin matrix did not detect any effect on inflammation.…”
Section: Discussionmentioning
confidence: 99%